110k views
0 votes
Find the inverse of the function:
f(x) = 3x + 6


User Hjd
by
4.4k points

2 Answers

6 votes

Answer:

x = -2

Explanation:

Pull out like factors :

-3x - 6 = -3 • (x + 2)

Solve : -3 = 0

This equation has no solution.

A a non-zero constant never equals zero.

Solve : x+2 = 0

Subtract 2 from both sides of the equation :

x = -2

User Patrick Lee
by
4.5k points
6 votes

The inverse of the funtion is f^-1(x)= x-6 over 3

Have a lovely day :)

User M Rijalul Kahfi
by
4.8k points